The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1007/s00418-011-0777-3
|View full text |Cite
|
Sign up to set email alerts
|

PI3K/Akt pathway mediates high glucose-induced lipogenesis and extracellular matrix accumulation in HKC cells through regulation of SREBP-1 and TGF-β1

Abstract: Previous studies have shown that high glucose stimulates renal SREBP-1 gene expression and increases renal tubular cells lipid metabolism, however, the mechanisms remain elusive. In the present study we demonstrated that PI3K/Akt pathway was activated in human renal proximal tubular cell line (HKC) exposed to high glucose accompanied with up-regulation of SREBP-1, TGF-β1, lipid droplets deposits and extracellular matrix production. Inhibition of PI3K/Akt pathway by chemical LY294002 or specific short hairpin R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 29 publications
(22 reference statements)
3
39
0
Order By: Relevance
“…Effects of inhibiting PI3K-Akt-mTOR pathway on de novo lipid synthesis Lipid biosynthesis is essential for the maintenance of cellular homeostasis. Accumulating evidence supports the idea that PI3K-Akt-mTOR pathway stimulates the lipid synthesis via inducing the expression of SREBP, which activates the transcription of the genes FAS and ACC, the two key enzymes of fatty acid biosynthesis (Laplante and Sabatini, 2010;Hao et al, 2011). Our previous studies demonstrated that overfeeding-induced elevated hepatic lipogenesis, accompanied with up-regulation of gene expression associating with de novo lipid synthesis, which was the main cause of fatty liver formation in goose (Han et al, 2008).…”
Section: Discussionmentioning
confidence: 64%
“…Effects of inhibiting PI3K-Akt-mTOR pathway on de novo lipid synthesis Lipid biosynthesis is essential for the maintenance of cellular homeostasis. Accumulating evidence supports the idea that PI3K-Akt-mTOR pathway stimulates the lipid synthesis via inducing the expression of SREBP, which activates the transcription of the genes FAS and ACC, the two key enzymes of fatty acid biosynthesis (Laplante and Sabatini, 2010;Hao et al, 2011). Our previous studies demonstrated that overfeeding-induced elevated hepatic lipogenesis, accompanied with up-regulation of gene expression associating with de novo lipid synthesis, which was the main cause of fatty liver formation in goose (Han et al, 2008).…”
Section: Discussionmentioning
confidence: 64%
“…In cultured renal tubular cells, high-glucose media could induce expression of SREBP-1 mRNA and protein levels, resulting in an enhanced cellular TG content through induction of FAS and ACC [22,49] . The relationship between SREBP-1 and an activated PI3K/Akt pathway has been confirmed in diabetic rats and in in vitro-cultured HKC cells [50] . Recently, mTOR was revealed to be involved in diabetic renal lipogenesis and could be a potential target for the treatment of DKD through regulation of SREBP-1 [51] .…”
Section: Srebp-1 Serves As a Mediator For The Crosstalk Between Glucomentioning
confidence: 70%
“…The molecular mechanism of the SB202190-mediated increases in SREBP-1 and FAS expression, and the involvement of p38 in TNF-a induced lipogenensis in sebocytes, remain to be solved. PI3K/Akt cell signaling is one of the key regulatory pathways for lipogensis in various cells including renal cells, prostate cells, hepatocytes, and adipocytes [30,[32][33][34], as well as in human sebocytes stimulated by insulin-like growth factor-1 [19]. During lipid synthesis, PI3K/ Akt regulates not only SREBP-1 activities at the transcriptional level [35] but also SREBP-1 cleavage activating protein (SCAP) activities [36]; the latter is a SREBP cleavage enzyme, whose activity leads to the maturation and translocation of SREBP-1.…”
Section: Discussionmentioning
confidence: 99%